PENGARUH MEDIA SOSIAL MARKETING TERHADAP CUSTOMER ENGAGEMENT DAN LOYALITAS PELANGGAN PADA UMKM DI KOTA KENDARI - Dzulfikri Azis Muthalib (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the effect of social media marketing on customer engagement and customer loyalty, as well as to examine the mediating role of customer engagement in the context of micro, small, and medium enterprises (MSMEs) in Kendari City. This research employs a quantitative approach using a survey method, with data collected from 50 MSME customers who actively interact through social media platforms. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that social media marketing has a positive and significant effect on customer engagement. Furthermore, social media marketing also has a positive and significant effect on customer loyalty. Customer engagement is proven to have a positive and significant effect on customer loyalty. Mediation analysis reveals that customer engagement partially mediates the relationship between social media marketing and customer loyalty. These findings suggest that effective social media marketing activities not only enhance customer loyalty directly but also indirectly through increased customer engagement.